Exogenous substances regulate silkworm fat body protein synthesis through MAPK and PI3K/Akt signaling pathways. (March 2017) - Tian, J.H.; Xue, B.; Hu, J.H.; Li, J.X.; Cheng, X.Y.; Hu, J.S.; Li, F.C.; Chen, Y.H.; Li, B.
Abstract: Insect fat body is an important intermediate metabolic organ that plays an important role in protein metabolism and detoxification. In order to study the effects of TiO2 NPs and phoxim on fat body protein synthesis through MAPK and PI3K/Akt signaling pathways in silkworms, we determined the effects of TiO2 NPs and phoxim, alone and in combination, on fat body protein content of silkworms, analyzed the gene expression profile of the fat body, and verified the expression of characteristic genes. We found that TiO2 NPs and phoxim alone increased the total protein content of the fat body, and up-regulated MAPK and PI3K/Akt signaling pathway genes. TiO2 NPs up-regulated the expression of two growth and development-related genes- insulin-like peptide and neuropeptide receptor B -by 5.17 and 3.89-fold, respectively. Phoxim up-regulated the expression of detoxification genes -P450, GST, and CarE2 . Pretreatment with TiO2 NPs could reduce phoxim-increased total protein content and up-regulated MAPK and PI3K/Akt signaling pathway genes and detoxification genes; the activities of detoxification enzymes were consistent with the gene expression pattern. Our results showed that MAPK and PI3K/Akt signaling pathways both regulate fat body protein synthesis in silkworms, but the target proteins induced to express were different under different inducing factors. Our finding may provide a reference for investigating the mechanism of protein synthesis regulation through MAPK and PI3K/Akt signaling pathways. Highlights: Phoxim and TiO2 NPs both cause up-regulation of total protein content through MAPK and PI3K/Akt Signaling Pathways. The up-regulation caused by Phoxim aims to detoxifcation. The up-regulation caused by TiO2 NPs aims to growth.